ADA APA DENGAN JILBAB? (SEBUAH PRAKTIK HEGEMONI MONOKULTURALISME DALAM INSTITUSI KEPOLISIAN) - Vellayati Hajad (Universitas Teuku Umar, 2016)
This article discusses the issue of the monocultural and hegemony that occur in police forces, especially police women in Indonesia. Monokulturalisme related to the concept of cultural unification (homogentitas). In monokulturalisme, a sign of the assimilation process is a mixture of two or more cultures to form a new culture. As an ideology, monokulturalisme in some countries serve as the basic of government policies and strategies concerning culture and system state.Keyword: Identity, Hegemony, Monokulturalisme